'People are Trying to be Modern': Food Insecurity and the Strategies of the Poor. Issue 3 (1st September 2016) - Leahy, Terry; Jean Brown, Debbie
Abstract : The failure of rural Africans to heed the message of development projects and improve agricultural practices is widely recognized as a problem in terms of food security and rural development. This study focuses on the situation in one locality of eastern Zambia and adopts a qualitative approach. By looking at local cultural issues a different understanding of the mechanisms of this failure may be attempted. We suggest that food provisioning is constructed in reference to an ideal of modernity in which subsistence production takes a particular (and gendered) relationship to the cash economy. The implication is that subsistence agriculture is conceived as 'reproduction' within capitalism rather than as a separate mode of production articulated with capitalism. This ideal of modernity and the associated utopia of food provisioning make it difficult for rural households in Zambia to see sustainable subsistence agriculture as any kind of a way forward.